Andantino, de Quincas Laranjeiras: fontes e critérios para uma nova edição (Orfeu, 2024)
In recent times, the guitar work by Joaquim Francisco dos Santos (1873-1935), Quincas Laranjeiras, has been reevaluated following the discovery of new sources, documents and scores (XXXX). Aiming to collaborate with this process, the article presents an unpublished manuscript of Andantino, a piece by Quincas that became known in the historiography of the instrument as Prelúdio em Ré Menor. Based on Figueiredo (2016), the text provides an overview of the work's history, surveys and compares the available sources (census and collation stages), highlighting the criteria that guided the choice of a musical base text and, as a result, the creation of a critical edition that aims to collaborate with the dissemination of the pioneering Brazilian repertoire for guitar.
Keywords: guitar pioneers; repertoire for guitar; guitar editions; guitar historiography; guitar in Rio de Janeiro